Factors influencing the willingness of community service organisation staff to provide smoking cessation support: a qualitative study - Ashleigh Parnell; Emily Box; Nicole Biagioni; Billie Bonevski; Julia Anwar‐McHenry; Terry Slevin; Simone Pettigrew (Elsevier, 2020)
Abstract Objective: This study aimed to explore factors influencing community service organisation (CSO) staff members' willingness to provide tobacco cessation support to clients experiencing disadvantage. Methods: Face‐to‐face semi‐structured interviews were conducted with 29 staff members from seven services in the alcohol and other drugs, homelessness, and mental health sectors in Western Australia. Results: The primary barriers to providing cessation support were believing that addressing smoking was not a priority relative to other issues, being a current smoker, and the lack of a formal tobacco cessation program within the organisation. Factors that appeared to be most influential in enabling the delivery of cessation support were organisational processes requiring staff to routinely ask clients about tobacco use, confidence to provide support, and being a past smoker. Conclusions: The introduction of organisational procedures that include routine cessation care should be of high priority in CSOs to help reduce smoking rates among clients. Staff may also benefit from receiving training in the provision of cessation support and education about the importance and feasibility of addressing smoking concurrently with other issues. Implications for public health: The results may inform future efforts to increase the delivery of cessation care to groups of people experiencing disadvantage and comorbidity.